Pengaruh Environmental Performance Dan Pengungkapan CSR Terhadap Nilai Perusahaan Terindeks LQ45 Non Keuangan Tahun 2020-2023 - Anggit Ayu Wibisono; Devi Astriani; Fista Apriani Sujaya (Akuisisi : Jurnal Akuntansi, 2026)
This study aims to analyze the influence of environmental performance and CSR disclosure on company value in LQ45 indexed issuers for the 2020-2023 period. The underlying phenomenon of this study is the fluctuation in CPIN companies with high levels of CSR and PROPER but experiencing a drastic decline in Price to Book Value (PBV), indicating different investor perspectives on CSR and PROPER implementation in the capital market context. This study uses a descriptive quantitative approach with secondary data obtained through a purposive sampling technique, resulting in 12 companies with a total of 48 samples. Data analysis was conducted using multiple linear regression tests based on the signaling and legitimacy theory framework. The results show that environmental performance partially has no positive effect on company value, while CSR disclosure partially has a significant positive effect. Simultaneously, both variables have a positive effect on company value. This study suggests that companies can optimize CSR disclosure as a strategy to increase company value, while regulators can consider increasing standards and incentives related to environmental performance to encourage more effective implementation by public companies in Indonesia.